EMPOWERING COLLEGE STUDENT ENTREPRENEURSHIP DURING THE PANDEMIC FOR ECONOMICS SUSTAINABILITY BY MAXIMIZING DIGITAL TECHNOLOGIES - Nuraeningsih Nuraeningsih; Rusiana Rusiana; Mamik Indaryani (Proceeding of the International Conference on Family Business and Entrepreneurship, 2021)
It is the first time ever in the world that the pandemic of Covid-19 highly contributes to the “limp” of almost all sectors including economics and education. College students are one of the “victims” that are now struggling with the challenges of online learning. As learning from home has been stipulated by the Ministry of Education and Culture, they have to welcome digitalization. In this case, they could make use of digitalization to actualize entrepreneurship to survive in this uneasy situation. Many positive things they could try to give small positive contributions to economics sustainability. This article aims at figuring out the student’ motivation in joining entrepreneurship Development Program (PPK) of Teacher Training and Education Faculty of Universitas Muria Kudus, how to empower college students entrepreneurship by maximizing digital technologies during the pandemic, and what business choices that the students choose and why. The participants are 20 college students from respective faculties. Survey, workshops, coaching and monitoring, and interview are used. An online survey was administered to figure out the students’ motivation to join the program. Then a series of online workshops were provided to facilitate the participants to set up new businesses. Coaching and monitoring have been doing since the selection of business type, business set up, production, and marketing by maximizing digital marketing. Interview was conducted to know the students’ reasons in deciding business types. From the whole participants, there are 8 businesses were launched. The few numbers of new entrepreneurs implies that motivationmatters. Keywords: college students, entrepreneurship, economic sustainability, digital technologies.